Basal Left Ventricular Dilatation and Reduced Contraction in Patients With Mitral Valve Prolapse Can Be Secondary to Annular Dilatation: Preoperative and Postoperative Speckle-Tracking Echocardiographic Study on Left Ventricle and Mitral Valve Annulus Interaction. (October 2016) - Fukuda, Shota; Song, Jae-Kwan; Mahara, Keitaro; Kuwaki, Hiroshi; Jang, Jeong Yoon; Takeuchi, Masaaki; Sun, Byung Joo; Kim, Yun Jeong; Miyamoto, Tetsu; Oginosawa, Yasushi; Sonoda, Shinjo; Eto, Masataka; et al.
Abstract : Background—: Prominent mitral valve (MV) annular dilatation with only modest left ventricular (LV) dilatation in patients with MV prolapse (MVP) suggests predominant dilatation in adjacent basal LV, which may augment regional wall tension and attenuate contraction by Laplace's law. We hypothesized that MV annular dilatation in patients with MVP is associated with the basal predominance of LV dilatation and attenuated contraction, which can be altered by surgical MV plasty with annulus reduction. Methods and Results—: Echocardiography with speckle-tracking analysis to assess regional cross-sectional short-axis area and longitudinal contraction (strain) of basal, middle, and apical LV was performed in 30 controls and 130 patients with MVP. The basal value/averaged middle and apical values (B/M·A ratio) of LV cross-sectional area and strain were obtained. Patients with MVP showed significantly greater MV annular area (6.4±1.6 versus 3.7±0.6 cm 2 /m 2 ), increased B/M·A LV area ratio (2.4±0.5 versus 1.8±0.2), and reduced B/M·A LV strain ratio (0.83±0.14 versus 0.96±0.09) than controls ( P <0.001). Multivariable analyses identified that MV annular dilatation was independently associated with increased B/M·A LV area ratio (β=0.60, P <0.001), which was associated with reduced B/M·A LV strain ratio (β=−0.32, P <0.001). In 35 patients with MVP, B/M·A LV area and strain ratio significantly altered after surgical MV plasty with annulus reduction (2.5±0.5–1.8±0.3 and 0.73±0.10–0.89±0.17, P <0.001, respectively). Conclusions—: In patients with MVP, MV annular dilatation was associated with the basal predominance of LV dilatation and reduced contraction, which can be altered by surgical MV plasty with annulus reduction, suggesting unfavorable influence from MV annular dilatation on basal LV. Abstract : Supplemental Digital Content is available in the text.